2022 Qatar World Cup: Impact Perceptions among Qatar Residents. (May 2017) - Al-Emadi, A.; Kaplanidou, K.; Diop, A.; Sagas, M.; Le, K. T.; Al-Ali Mustafa, S.
The purpose of this study was to evaluate how the impacts from the 2022 World Cup preparations in Qatar influenced local residents' attitudes, personal and community quality of life perceptions, excitement about hosting the event, and support toward the event. The examination of the way mega sport event impacts influence residents' perceptions of personal and community quality of life is lacking in the literature. Data were collected using systematic sampling in October 2014 from Qatari nationals and white-collar expatriates. Overall, 2, 163 interviews with Qatari nationals (1, 058) and white-collar expatriates (1, 105) were completed. The results revealed that eight years before the event, sociocultural impacts were the most influential type of impact for residents' attitudes toward the event, community and personal quality of life, excitement about the event, and support of the FIFA decision to host the event in Qatar.